Inclusão no IF Farroupilha Campus Santo Augusto: conjunto de práticas políticas que tem produzido sujeitos - Gattermann, Beatris (2017)
The present study is part of the research field of inclusion policies implemented in the Federal Institutes of Professional Education in Brazil and specifically in the Farroupilha Federal Institute. It can be included among the studies that use a post-structuralist perspective, based on the Foucaultian Studies especially the notions of governmentality, regulation and standardization for procedure and analytical development. It aims to identify and understand how the strategies of permanence and learning put into operation are producing other ways of saying about the student in a situation of non-learning. Methodologically for analysis was taken as basis the model of the inclusive policies devised in a discursive network for professional education and the possibility to untangle the ways to observe the part of the void that a pulled line causes in the model. Thus, in the first analytical unit, the study points to a set of international documents and it seeks to identify how the adoption of inclusion, as a way of determining of the conditions for education in the present time, can be explained in the order of neoliberal governmentality and how certain conditions of possibility are built for the reform in the professional education and creation of the Federal Institutes in Brazil. The second unit, shows the analysis of the discourses present in the IFFar documents that operate as a way of capturing young people for professional education. It verifies the emergence of inclusion discourses and learning as useful discourses for the management of student learning and permanence in vocational education. Finally, in the face of the emptiness left in the complex model of professional education, it becomes possible to show the discursive practices and tactics that take learning as a strategy of inclusion, in a discourse that is updated in the present, in relation to (in) exclusion and the production of people in situations of non-learning.